Archived Formalin-Fixed Paraffin-Embedded (FFPE) Blocks: A Valuable Underexploited Resource for Extraction of DNA, RNA, and Protein - Kokkat, Theresa J. (Mary Ann Liebert, Inc., 2013)
Formalin-fixed paraffin-embedded (FFPE) material presents a readily available resource in the study of various biomarkers. There has been interest in whether the storage period has significant effect on the extracted macromolecules. Thus, in this study, we investigated if the storage period had an effect on the quantity/quality of the extracted nucleic acids and proteins. We systematically examined the quality/quantity of genomic DNA, total RNA, and total protein in the FFPE blocks of malignant tumors of lung, thyroid, and salivary gland that had been stored over several years. We show that there is no significant difference between macromolecules extracted from blocks stored over 11–12 years, 5–7 years, or 1–2 years in comparison to the current year blocks.